Performance and emissions of compression ignition engine fueled with preheated blend of vegetable oil - Suffian, Mohamad Mokhsen (2014)
Now days fossil fuel has been a problem that can been use in a compression ignition engine. Straight vegetable oil is one of the most reliable fuel that suitable for diesel engine. The scope of study of this study is focused on performance and emission of the straight vegetable oil from the grocery store to compare with crude palm oil from UTHM pilot plan. S5, S10 and S15 straight vegetable oil fuel is used for this experiment. This straight vegetable oil is also compared with an natural diesel in a combustion-ignition engine. The test is conducted with UTHM dynomometer which is located at automotive lab. The properties of the vegetable oil is tested for density, kinematic viscosity, water content, acids value and flash points. Brake power, flywheel torque, (in term of hydrocarbon, carbon monoxide, carbon dioxide, oxygen content and smoke opacity) and tested for performance and emission. Results obtained show that flywheel torque that has been produced from the biodiesel fuels are less than the natural diesel (ND). Biodiesel emission results shown a better emission compared to the ND fuels. The CO2, CO, HC and O2 content that released from the biodiesel fuels are clearly lower than the ND fuels. At low engine speed, biodiesel smoke opacity contents are quite high produces compared to the OD and other type of